Wrack placement to augment constructed dunes: A field investigation - Provost, Leigh A.; Eisemann, Eve R.; Anderson, Carlton P.; Waldron, Margaret C. B. (Frontiers in Built Environment, 2022)
Natural and nature-based features have become increasingly popular in recent years for several 11 reasons including reduced costs and maintenance, sustainability, and ecological benefits. One such 12 nature-based feature which contributes to coastal resiliency is dune systems. Extensive research has 13 occurred in recent years citing the value provided by dune systems to coastal protection, and further 14 investigate the role of vegetation in dune stability. Additionally, several alternative dune construction 15 and dune maintenance methods have been investigated to further encourage resilience and stability of 16 natural dune systems. This manuscript documents preliminary results following the application of a 17 wrack placement procedure implemented in a test region along the Mississippi Coast in Harrison 18 County. Terrestrial lidar surveys were executed to evaluate the behavior of a 550 meter test region, 19 with varying grooming and wrack management practices implemented. The elevations and 20 volumetric changes from these data were compared relative to significant storm events impacting the 21 area to quantify the potential benefits of alternative management strategies. Significant results from 22 the 19-month monitoring study demonstrated the following: 23 ● Net volumetric change in the study area from project inception resulted in erosion across the 24 berm, ramp and dune regions and all monitoring zones, with the exception of the non-25 groomed zone and the non-groomed and treated zone in the ramp region, though total 26 sediment lost was reduced in the non-groomed zone and the non-groomed and treated zone of 27 the berm and dune regions. 28 ● Accretive and erosive trends between surveys vary broadly with varying storm events. 29 ● During recovery periods, time periods that did not see significant storm impacts, the treated 30 zone of the project area saw accretion within the dune region.